Study of treatment outcome of tuberculosis among HIV co-infected patients: a cross sectional study in Aurangabad city, Maharashtra - Warkari, Prashant D.; Nakel, Mahavir P.; Mahajan, Swati M.; Adchitre, Sangita A. (International Journal Of Community Medicine And Public Health, 2017)
Background: Tuberculosis is the most common presenting illness among people living with HIV, including those who are taking anti-retroviral treatment. There were an estimated 1.2 million HIV positive new TB cases globally in 2014. Around 74% of these infected people live in sub-Saharan Africa. Aim and objectives were to study the treatment outcome of tuberculosis among HIV co-infected patients; to assess the outcome of TB treatment in TB patients with respect to their HIV status and to study the underlying factors influencing the outcome rates. Methods: A descriptive cross-sectional study was designed and conducted in Municipal Corporation area, Aurangabad. For this study, HIV co-infected patients registered at city Tuberculosis Centre, Aurangabad were noted and thus information only on TB-HIV status of patients was collected. Results: In this study majority of the study participants were in the age group between 35 and 49 years (45.98%); which is in the reproductive age group. HIV-TB co-infected in this region was mostly males (60.92%). Conclusions: Important conclusion of the study is that very few patients got cured off TB among TB-HIV co-infected patients. One of the reasons could be immunosuppression of HIV patients make them vulnerable for getting active TB and its rapid progression. All the rates i.e. death, default & transfer rate are all above the standard rate i.e. 5% as per RNTCP guidelines.